SIFO 1989: Motor traffic in big cities - Swedish Institute of Public Opinion Research; Rapport/TV2 (Swedish Institute of Public Opinion Research, 1993)
This study, carried out by the Swedish Institute of Public Opinion Research (SIFO) at the request of the news program Rapport at TV2, deals with the respondent´s attitudes toward inner-city tolls and also toward regulations of the traffic in big cities as Stockholm, Göteborg and Malmö, and in the respondent´s own town or municipality. The respondent also had to indicate the consequences of motor traffic on public transport, and if one has to accept a poorer environment in consequence of motorism. Background variables include information on gender, place of living, age, Swedish citizenship, occupation, private or public sector, trade union, right to vote in general elections, voting habit, political party preference and party voted for in 1988.

SIFO genomförde denna undersökning på uppdrag av Rapport/TV2. Frågorna som ingick i SIFO-buss 89085 behandlar respondenternas inställning till bilismen i storstäder respektive sin egen hemkommun - bör biltrafiken förbjudas, tillåtas men begränsas, vara som den är eller ska en ökning tillåtas. Vidare tillfrågades man om det vore bra att införa avgifter för att köra bil i stora städers centrala delar och om man tror att politikerna i så fall kommer att satsa mera på kollektivtrafiken. Avslutningsvis fick man ange om man tycker att man måste acceptera en sämre miljö till följd av bilismen om man bor i en stads centrala delar.
Bakgrundsvariablerna inkluderar frågor om kön, bostadsort, ålder, svenskt medborgarskap, sysselsättning, privat eller offentlig arbetsgivare, facklig anslutning samt partipreferens.
SIFO 1989: Biltrafiken i storstäder
Keywords: public transport; kollektivtrafik; travel; resor; cars; bilar; environment policy; miljöpolitik; Environment and conservation; Miljö och naturvård; TRANSPORT AND TRAVEL; TRANSPORT OCH RESOR; Social Sciences; Samhällsvetenskap